On the need of distinguishing ductile and brittle failure modes in timber connections with dowel-type fasteners. (1st September 2021) - Yurrita, Miguel; Cabrero, José Manuel
Highlights: Timber connections with dowel-type fasteners may fail in ductile and brittle ways. The Eurocode 5 combines ductile (EYM) and britte (nef ) in the same calculation. Two calculations models are desirable to identify the expected failure mode. Accurate models are needed for that. The Eurocode 5 approach is conservative. A proposal to improve current accuracy and discrimination ability is given. Abstract: Timber connections can fail in a ductile or in a brittle way. A structural design that guarantees a ductile behaviour in case of failure is desirable, especially when facing extreme situations such as earthquakes. This work discusses how the European Yield Model (based on a ductile failure mechanism), included in many standards, combined with a reduction of the effective number of fasteners may provide too conservative results, which may inadvertently lead to risky situations in which a connection assumed to fail under a ductile mechanism would actually fail in a brittle manner. Within this paper, a proposal to improve the discrimination ability to correctly predict the failure mode is proposed.